The Last Tyrants of Athens - Borja Antela (Karanos, 2019)
This paper deals with the complex situation that lived Athens at the first decades of the Ist Century BC. Between the good and advantageous relations with Rome, that led Athens to big benefits from the control of the Delian markets, and the hard sack of the city by the troops of Sulla in March 86, the city suffered an economical crisis that derived in political instability. The government of Athens finally was hold by some persons who acted like tyrants, in a moment when events and historical context (social conflict and economical crisis) seems to remember the situation that produced the historical phenomenon of the Greek Tyranny.